Robust Packing of a Self‐Assembling Iridium Complex via Endocytic Trafficking for Long‐Term Lysosome Tracking. (1st March 2021) - Jin, Chengzhi; Li, Guanying; Wu, Xia; Liu, Jiangping; Wu, Weijun; Chen, Yazhou; Sasaki, Toshio; Chao, Hui; Zhang, Ye
Abstract: Live cell imaging of lysosome positioning and motility is critical to studying lysosome status and function for pharmacological interventions. To create a super stable lysosomal probe for long‐term live cell imaging, we have designed and synthesized an aromatic‐peptide‐conjugated cyclometalated iridium(III) complex that emits light via π–π stacking oriented self‐assembly in water at extremely low concentration. Through endocytic trafficking, self‐assemblies are transformed from nanoparticles into sturdily packed networks that are stabilized in lysosomal acidic environment. Upon short time/low dose treatment of the iridium complex at passage 0, live cell lysosomal tracking is applicable beyond the 14th passage of cells with high labelling rate and a mild decline in luminescence intensity. The illuminated lysosomes are trackable using super‐resolution imaging to study their response to cellular processes. Abstract : An aromatic‐peptide‐conjugated cyclometalated iridium(III) complex has been synthesized that emits light via π–π stacking oriented self‐assembly at extremely low concentration. Through endocytic trafficking, self‐assemblies are transformed from nanoparticles into sturdily packed networks that are stabilized in lysosomal acidic environment as super stable lysosomal probes, enabling super long‐term live cell imaging.